A Review of Malicious Node Detection in Mobile Ad-hoc Networks - Punwatkar, Dipali D; Hande, Kapil N (International Journal of Computer Sciences and Engineering, 2014)
Ad-hoc networks are a new paradigm of wireless communication for mobile hosts where node mobility causes frequent changes in topology. Ad hoc networks are self-configurable and autonomous systems consisting of routers and hosts, which are able to support movability and organize themselves arbitrarily. Moreover, other characteristics such as frequent changes of the topology, nodes limitations like energy resource, storage device, CPU and communication channel limitations like bandwidth, reliability add extra challenges. Mobile ad hoc networks aimed to propose solutions to some fundamental problems, such as routing, coping with the new challenges caused by networks and nodes features without taking the security issues into account. Hence, all these solutions are vulnerable to threats. Any node under attack in ad hoc network exhibits an anomalous behavior called the malicious behavior. This paper is a survey on different malicious node detection mechanisms, and the security problems caused due to malicious nodes in mobile ad hoc networks.